"Pater Aeneas, romanae stirpis origo...". Mit o Eneaszu i jego obecność w literaturze epoki Augusta = "Pater Aeneas, romanae stirpis origo?". The myth of Aeneas and his presence in the literature of the age of Augustus - Kluska-Jaśkowiak, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the reception of the myth about Aeneas as the father of the Roman nation in the literature of the Augustus age. The issue was developed based on the analysis of a selected source mate?rial produced in the Augustan age. Particular attention was paid to representative examples, which use the story of Aeneas in literature, in order to define the role and functions of the Trojan in the political program of Augustus.
Keywords: epoka augustowska; Eneasz; Eneida; ojciec narodu; Augustus age; Aeneas; Aeneid; father of the Roman nation